Những câu hỏi liên quan
DL
Xem chi tiết
TH
15 tháng 4 2022 lúc 8:49

\(A=\left(x+y\right)\left(x+3y\right)\left(x+5y\right)\left(x+7y\right)+16y^4\)

\(=\left(x^2+8xy+7y^2\right)\left(x^2+8xy+15y^2\right)+16y^4\)

\(=\left(x^2+8xy+7y^2\right)^2+8y^2\left(x^2+8xy+7y^2\right)+16y^4\)

\(=\left(x^2+8xy+7y^2+4y^2\right)^2=\left(x^2+8xy+11y^2\right)^2\)

-Vậy A là số chính phương với mọi x,y nguyên.

 

Bình luận (0)
PS
Xem chi tiết
PK
Xem chi tiết
NP
19 tháng 7 2016 lúc 20:36

\(4x=7y\Rightarrow\frac{x}{7}=\frac{y}{4}\)

\(\Rightarrow\frac{x^2}{49}=\frac{y^2}{16}=\frac{x^2+y^2}{49+16}=\frac{260}{65}=4\)

\(\Rightarrow\hept{\begin{cases}x^2=196\\y^2=64\end{cases}}\)

Với x=-14 thì y=-8\(\Rightarrow x+y=\left(-14\right)+\left(-8\right)=-22\)

Với x=14 thì y=8\(\Rightarrow x+y=14+8=22\)

Bình luận (0)
TL
Xem chi tiết
LL
1 tháng 11 2021 lúc 22:38

1D  2C

Bình luận (0)
NT
1 tháng 11 2021 lúc 22:39

Câu 1: D

Câu 2: C

Bình luận (0)
TL
Xem chi tiết
NT
14 tháng 5 2022 lúc 23:36

a: \(=\dfrac{2x-2x+y}{2\left(2x-y\right)}=\dfrac{y}{2\left(2x-y\right)}\)

b: \(=\dfrac{3x+1}{\left(x-1\right)\left(x+1\right)}-\dfrac{x}{2\left(x-1\right)}\)

\(=\dfrac{6x+2-x^2-x}{2\left(x-1\right)\left(x+1\right)}\)

\(=\dfrac{-x^2+5x+2}{2\left(x-1\right)\left(x+1\right)}\)

c: \(=\dfrac{1}{x+2}+\dfrac{x+8}{3x\left(x+2\right)}\)

\(=\dfrac{3x+x+8}{3x\left(x+2\right)}=\dfrac{4x+8}{3x\left(x+2\right)}=\dfrac{4}{3x}\)

d: \(=\dfrac{4x+6-2x^2+3x+2x+1}{\left(2x-3\right)\left(2x+3\right)}\)

\(=\dfrac{-2x^2+9x+7}{\left(2x-3\right)\left(2x+3\right)}\)

Bình luận (0)
QL
Xem chi tiết
HM
17 tháng 9 2023 lúc 15:38

a) \(\begin{array}{l}(8{x^3} + 2{x^2} - 6x):(4x) = 8{x^3}:(4x) + 2{x^2}:(4x) - (6x):(4x)\\ = (8:4).({x^3}:x) + (2:4).({x^2}:x) - (6:4).(x:x)\\ = 2{x^2} + \dfrac{1}{2}x - \dfrac{3}{2}\end{array}\)

b) \(\begin{array}{l}(5{x^3} - 4x):( - 2x) = 5{x^3}:( - 2x) - 4x:( - 2x) = (5: - 2).({x^3}:x) - (4: - 2).(x:x)\\ =  - \dfrac{5}{2}{x^{3 - 1}} - ( - 2) =  - \dfrac{5}{2}{x^2} + 2\end{array}\)

c) \(\begin{array}{l}( - 15{x^6} - 24{x^3}):( - 3{x^2}) = ( - 15{x^6}):( - 3{x^2}) + ( - 24{x^3}):( - 3{x^2})\\ = ( - 15: - 3).({x^6}:{x^2}) + ( - 24: - 3).({x^3}:{x^2})\\ = 5.{x^{6 - 2}} + 8.{x^{3 - 2}} = 5{x^4} + 8x\end{array}\)

Bình luận (0)
DM
Xem chi tiết
PA
Xem chi tiết
TH
4 tháng 3 2017 lúc 20:46

\(A+B=x^3+x^2y-5^2+10xy+7y^3+8+y^3-3x^2y+6y^2+2xy^2-19xy-8x^3+2.\)

\(=x^3-8x^3+x^2y-3x^2y+10xy-19xy+7y^3+y^3+6y^2+2xy^2-25+8+2.\)

\(=-7x^3-2x^2y-9xy+8y^3+2y^2\left(3+x\right)-15.\)

Bình luận (0)
NL
Xem chi tiết
NT
9 tháng 1 2023 lúc 7:47

4x=7y nên x/7=y/4

Đặt x/7=y/4=k

=>x=7k; y=4k

xy=112

=>28k^2=112

=>k^2=4

TH1: k=2

=>x=14; y=8

TH2: k=-2

=>x=-14; y=-8

Bình luận (0)